1988
DOI: 10.1159/000128764
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the Histology of Normal Spleen and That of Regenerated Ectopically Implanted Splenic Tissue

Abstract: The histology of regenerated ectopically implanted spleen (splenotic tissue) from splenectomized rats was compared with that of normal rat spleen. Computer-assisted morphometric analysis revealed significant decreases in both the number and area of splenic nodules in splenotic tissue when compared with normal spleen. It is suggested that the reduction in the amount of white pulp present could explain at least in part the reduced ability of splenotic tissue to deal with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Splenic autotransplantation could be a mechanism to restore, at least in part, splenic function after splenectomy. The pattern of splenic regrowth has been described by light (Perla, 1936 ;Cameron & Rhae, 1959 ;Chen, 1978 ;Dijkstra & Langevoort, 1982 ;Lau & Ong, 1983 ;Felle, 1988 ;Johnson & Weiss, 1989 ;Carr & Turk, 1992) and electron microscopy (Sasaki, 1986 ;Sasaki et al 1991). Neovascularisation studies on mouse splenic implants have shown that after a few days central necrosis occurs and vessels around the implant begin to grow towards the internal vessels, later connecting with them.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Splenic autotransplantation could be a mechanism to restore, at least in part, splenic function after splenectomy. The pattern of splenic regrowth has been described by light (Perla, 1936 ;Cameron & Rhae, 1959 ;Chen, 1978 ;Dijkstra & Langevoort, 1982 ;Lau & Ong, 1983 ;Felle, 1988 ;Johnson & Weiss, 1989 ;Carr & Turk, 1992) and electron microscopy (Sasaki, 1986 ;Sasaki et al 1991). Neovascularisation studies on mouse splenic implants have shown that after a few days central necrosis occurs and vessels around the implant begin to grow towards the internal vessels, later connecting with them.…”
Section: mentioning
confidence: 99%
“…No microspheres were found inside the vessels emerging from the surrounding tissues and entering the implant up to 3 d after surgery. Some dilated vascular structures, called ' vascular spaces ' (Felle, 1988), developed under the capsule of the autografts as early as 2 d after the implant. Such structures could persist over the next few days, but were devoid of microspheres.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Splenotic tissue has a decreased amount of white pulp, 51,52 and while it contains many elements of the normal spleen, the splenic nodules are smaller in mass with reduced individual compartments. 47 The reduced immune function of these ectopic implants may be partially related to the decreased amount of white pulp.…”
Section: 87-90mentioning
confidence: 99%
“…Autotransplanted slices were 30 grams and placed in extraperitoneal pockets. Splenic reticuloendothelial dysfunction was measured using a pocked erythrocyte assay (as gauged by interference-phase microscopy) and erythrocyte clearance using 51 Cr-labeled autologous antibody-coated erythrocytes. Splenic dysfunction was indicated by an increase in pocked erythrocytes and less erythrocyte clearance.…”
mentioning
confidence: 99%